Mediating role of gestational weight gain in the relationship between socioeconomic status and preterm birth: a Chinese population-based study - Xiaomei Xiang; Yan Huang; Ziping Wang; Zongkai Li; Shaonong Dang (BMC, 2024)
Abstract Background The modifiable mechanisms underlying the association between socioeconomic status (SES) and preterm birth remain unclear. This study aimed to investigate the relationship between preterm birth and maternal SES or gestational weight gain (GWG), as well as the role of GWG in mediating SES disparities in preterm birth. Methods Data was from a hospital-based sub-study of physical growth and development survey for Chinese newborns with various gestational ages. Singleton newborns aged from 24 to 42weeks' gestation and their mothers were included. Using information from maternal questionnaire, a composite SES was constructed with parental education and family annual income. GWG as mediator was calculated by deducting pre-pregnancy weight from maternal weight at delivery. Logistic regression model was adopted to investigate the association of preterm birth with SES or GWG. Causal mediation analysis was performed to measure mediating effect of GWG on the pathway from SES to preterm birth. Results After controlling for potential confounders, risk of preterm birth was reduced by 12.4% (OR = 0.876, 95%CI:0.855-0.879) for per one-kilogram increase of GWG, and risk of preterm birth was reduced by 24% (OR = 0.760, 95%CI: 0.717-0.806) for per one-unit increase of SES score. Mediation analysis supported a significant association between higher SES and decreased risk of preterm partly through higher GWG, in which estimated proportion mediated by GWG was 13.04% (95%CI: 11.89-16.25). GWG also played a significant role as a mediator when socioeconomic status was indicated by maternal education, paternal education or family income. GWG mediated approximately 11.03% (95% CI: 8.56-18.25) of the total effect of SES on very preterm birth, which was greater than that for moderate preterm birth (6.72%, 95%CI: 2.72-31.52) and late preterm birth (9.04%, 95%CI: 5.24-24.04). A series of sensitive analysis confirmed the robustness of association of interest. Conclusion Increased GWG and higher socioeconomic status are strongly associated with a lower risk of preterm birth. GWG mediates socioeconomic disparities in preterm birth, most notably in very preterm birth. Understanding this mechanism will aid in the development of interventions and policy for maternal and child health care.